Implementation of Public Service Innovation in Dynamic Governance of Dukcapil Pekanbaru City - Sufi, Wasiah (Journal of Education on Social Science (JESS), 2023)
Institutional or governmental innovation is a benchmark in carrying out a dynamic governance perspective. It is intended that the government is able to implement these policies with dynamic changing conditions. This research intends to add an explanation of how the concept of dynamic governance is applied in public service innovation in local government organizations. One interesting case to be elaborated in this research is public service innovation in one of the Pekanbaru City regional apparatus organizations, namely the Population and Civil Registration Office, which applies many dynamic governance principles. The purpose of this study is to determine the success and failure of the application of public service innovation in the perspective of dynamic governance in Pekanbaru City, which conducts a study at the Population and Civil Registration Office. This research uses the theory of Service Innovation according to Rogers and the theory of dynamic governance according to Boon and Geraldine This research uses qualitative research methods with case study methods. Researchers use case studies with intrinsic types. This type is research conducted on the basis of interest in a particular case. In this case, researchers see how the form of application of public service innovation in the perspective of dynamic governance in Pekanbaru City. The results obtained from this study are the successes and failures found in each instrument of service innovation in the perspective of dynamic governance.